Paroxysmal hypertension with reversible posterior leukoencephalopathy syndrome in a child: an unresolved riddle - Thomas, Mili; Nair, Veena V.; Hrishikesan, Lekha; Swarnam, Kamala (International Journal of Contemporary Pediatrics, 2019)
Nine year old girl was presented with paroxysmal episodes of hypertensive emergency. She was asymptomatic with normal blood pressure without antihypertensives in between the episodes. MRI brain was suggestive of reversible posterior leukoencephalopathy. Acute episodes were managed with IV labetalol infusion and amlodipine. She was evaluated extensively to find out the etiology of hypertension. Cardiac and renal causes were ruled out. Work up for pheochromocytoma, hyperaldosteronism, porphyria and vasculitis were negative. The case is reported in view of the rare presentation and the leukoencephalopathy noted in this case.